2016
DOI: 10.3389/fphys.2016.00065
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TRPV4 Regulates Respiration through Indirect Activation of Bronchopulmonary Sensory Neurons

Abstract: Transient receptor potential vanilloid receptor 4 (TRPV4) is a calcium-permeable non-selective cation channel implicated in numerous physiological and pathological functions. This study aimed to investigate the effect of TRPV4 activation on respiration and to explore the potential involvement of bronchopulmonary sensory neurons. Potent TRPV4 agonist GSK1016790A was injected into right atrium in anesthetized spontaneously breathing rats and the changes in breathing were measured. Patch-clamp recording was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
4
12
0
Order By: Relevance
“…Additionally, the TRPV4 channel was found to mediate neutrophil activation and acute lung injury (Yin et al, ). We found that TRPV4‐immunopositive cells co‐localized with the macrophage marker F4/80 (Supporting Information Figure S1A), which agrees with previous findings in alveolar macrophages (Gu et al, ). We also detected TRPV4‐ and F4/80‐double labelled cells in the bone marrow (Supporting Information Figure S1B).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the TRPV4 channel was found to mediate neutrophil activation and acute lung injury (Yin et al, ). We found that TRPV4‐immunopositive cells co‐localized with the macrophage marker F4/80 (Supporting Information Figure S1A), which agrees with previous findings in alveolar macrophages (Gu et al, ). We also detected TRPV4‐ and F4/80‐double labelled cells in the bone marrow (Supporting Information Figure S1B).…”
Section: Discussionsupporting
confidence: 91%
“…We used 1% DMSO / 20% Captisol (sulfobutyl ether‐β‐cyclodextrin) in saline as the vehicle, as described previously (Willette et al, ). The GSK1016790A dose selected should not affect the cardiovascular system, as demonstrated previously (Pankey et al, ; Gu et al, ).…”
Section: Methodssupporting
confidence: 57%
“…The primary N/J ganglionic neurons were cultured as reported previously (39). Briefly, after decapitation, the rat head was immediately immersed in ice-cold DMEM/F12 solution, followed by quick extraction of N/J ganglia under a dissecting microscope.…”
Section: Cultured Laryngeal C Neurons In the N/j Gangliamentioning
confidence: 99%
“…Animal handling and experiments were conducted in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals, and the ARVO Statement for the Use of Animals in Ophthalmic and Vision Research, with the project also approved by the Institutional Animal Care and Use Committee at the University of Utah. C57BL/6 (C57), TRPV4 −/− , 30 and B6.Cg-Gt(ROSA)26Sortm9(CAGtdTomato) Hze/J (Ai9) in which the LoxP-STOP-LoxP TdTomato construct is knocked in at the Gt(ROSA)26Sor locus (referred to as TRPV1 tdT ) 31 and bacterial artificial chromosome (BAC)-transgenic Tg(TRPV4-EGFP)MT43Gsat mice (referred to as TRPV4 eGFP ) mice 32 were maintained in a pathogen-free facility with a 12-hour light/dark cycle and unrestrained access to food and water. Data were gathered from 1-to 3-month-old male and female animals with no noted gender differences.…”
Section: Ethical Approval and Animalsmentioning
confidence: 99%